The Zakat and Technology - Nailah Nailah; Aam Slamet Rusydiana (Center of Strategic Studies (PUSKAS) BAZNAS, 2020)
This study aims to determine the development and trend map of the Zakat and Technology outbreak research that is published by reputable journals in the theme of Islamic economics and finance. The data analyzed covering more than 440 publications of indexed research publications. The export data is then processed and analyzed using the R Biblioshiny application program to find out the bibliometric map of the development of the role of Islamic economics and finance in zakat and technology research. The results showed that the number of publications on the development of the role of Islamic economics and finance research experienced a significant increase. The results show that the highest number of document types are journaled articles. The most popular authors are Kuran T, and the most popular keyword topics are zakat, Islam, and Indonesia.